Implementation of Standardized Assessment Management to Improve the Quality of Islamic Education - Lina Sukanti (The International Journal of Education Management and Sociology, 2022)
This study is based on an effort to improve the quality of education by implementing assessment standard management in the teaching and learning process. The focus of this research is the implementation of assessment standard management to improve the quality of Islamic education for high school graduates in South Tangerang. While the purpose of this study is to describe the planning, implementation, evaluation, problems faced, and standard assessment solutions to improve the quality of high school graduates in South Tangerang. This research uses a qualitative naturalistic approach and descriptive method. Data collection techniques are conducted utilizing interviews, observations, and documentation studies. The results of this study are as follows: (1). Management of assessment standards was prepared through the planning stage, which describes the Learning Implementation Plan. (2). Organizing describes the role of principals, educators, educational personnel, learning load management, attitude value determination, knowledge value determination, and skill value determination. (3). The implementation stage outlines the principles of value, assessment procedures, assessment techniques, assessment time, learning completion, and competence of graduates. (4). The evaluation phase outlines the assessment standards, class increase criteria, implementation and reporting of assessments by education units, and remedial, enrichment, and graduate criteria. (5). The problem faced is that educators have difficulty in determining Minimum Completion Criteria, Class Ascension Criteria, and Graduation Criteria. (6). Efforts are made to conduct a lot of socialization and training on assessment standards and assessment guidelines, especially related to Minimum Completion Criteria, Class Increase Criteria, and Graduation Criteria.